The Effectiveness Of Youtube Media In Increasing Students' Motivation And Interest In Fiqh Learning In The Digital Era - Aulia Indah Wahyu Nurlailla; Muhammad Dwi Toriyono (Journal of Education and Learning Sciences, 2026)
The era of digitalization requires teachers to innovate in learning, yet most still use outdated methods to deliver material to students. The lack of innovation in the learning process makes students feel bored, leading to a low impact on their motivation and learning interest. One step to address this is to integrate media and methods into the learning process. This study aims to test the effectiveness of YouTube media in increasing students' motivation and interest in learning fiqh subjects. The study uses a quantitative approach with a quasi-experimental design (pretest-posttest control group). Data collection was conducted using questionnaires and documentation, which were analyzed using a MANOVA test in SPSS software version 25. The results of the data analysis showed Sig. 0.000 < 0.05 in both variables, which means that YouTube media affects learning motivation with a Partial Eta Squared value of 0.211 and learning interest with a Partial Eta Squared value of 0.298. The Partial Eta Squared indicated that the use of YouTube media in fiqh subjects contributed 21.1% to learning motivation and 29.8% to learning interest. Based on the interpretation of Partial Eta Squared, the results indicate large effects, suggesting that YouTube learning media can be applied in the learning process as a new form of innovation in the digital era.